Clinical features related to hospital expenses for non-cystic fibrosis bronchiectasis in China. Issue 6 (June 2020) - Ma, Yanliang; Liu, Daishun; Ji, Yingqun; Wei, Xuemei; Pan, Dianzhu; Xu, Fei; Di, Qingguo; Chen, Xiaoju; Luo, Fengming; Zhang, Jiujin; Ou, Guiying; Zhang, Yan; et al.
Objective: Bronchiectasis is a common chronic airway disease. We investigated the economic burden and associated factors of bronchiectasis in China. Methods: In this multicenter retrospective cohort study, we reviewed medical records of patients admitted to 18 tertiary hospitals during 2010 to 2014 with a bronchiectasis-related diagnosis. Results: A total 5469 patients with bronchiectasis were admitted, accounting for 3.13% ± 1.80% of all discharged patients with any diagnosis during the same period; 13 patients died upon discharge. The median hospitalization cost was RMB 8421.52 (RMB 5849.88–12, 294.47). Risk factors associated with hospitalization costs included age at admission (>70 vs. <40 years, odds ratio (OR) = 1.221, 95% confidence interval (CI) = 1.082–1.379; >80 vs. <40 years, OR = 1.251, 95% CI = 1.089–1.438), smoking (≤15 packs/year vs. non-smokers, OR = 1.125, 95% CI = 1.006–1.271; >15 packs/year vs. non-smokers, OR = 1.127, 95% CI = 1.062–1.228), length of hospitalization (OR = 1.05, 95% CI = 1.046–1.054), combination antibiotic treatment (OR = 1.089, 95% CI = 1.033–1.148), cough (OR = 0.851, 95% CI = 0.751–0.965), dyspnea (OR = 0.93, 95% CI = 0.878–0.984), chronic obstructive pulmonary disease (OR = 0.935, 95% CI = 0.878–0.996), respiratory failure (OR = 0.923, 95% CI = 0.862–0.989), cor pulmonale (OR = 0.919, 95% CI = 0.859–0.982), and death (OR = 1.816, 95% CI = 1.113–2.838). Conclusions: Age, smoking status, symptoms, and respiratory comorbidities were associated with hospitalization costs of bronchiectasis.